Fine particles, genetic pathways, and markers of inflammation and endothelial dysfunction: analysis on particulate species and sources - Dai, Lingzhen (J Expo Sci Environ Epidemiol, 2016)
BACKGROUND: Studies have found associations between PM(2.5) and cardiovascular events. The role of different components of PM(2.5) is not well understood. METHODS: We used linear mixed-effects models with the adaptive LASSO penalty to select PM(2.5) species and source(s), separately, that may be associated with markers of inflammation and endothelial dysfunction, with adjustment for age, obesity, smoking, statin use, diabetes mellitus, temperature, and season as fixed effects, in a large longitudinal cohort of elderly men. We also analyzed those associations with source apportionment models and examined genetic pathway-air pollution interactions within three relevant pathways (oxidative stress, metal processing, and endothelial function). RESULTS: We found that independent of PM(2.5) mass vanadium (V) was associated with intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1). An IQR increase (3.2 ng/m(3)) in 2-day moving average V was associated with a 2.5% (95% CI: 1.2 – 3.8%) change in ICAM-1, and a 3.9% (95% CI: 2.2 – 5.7%) change in VCAM-1, respectively. Additionally, an oil combustion source rich in V was linked to these adhesion molecules. People with higher allelic risk profiles related to oxidative stress may have greater associations (p-value of interaction = 0.11). CONCLUSIONS: Our findings suggest that particles derived from oil combustion may be associated with inflammation and endothelial dysfunction, and it is likely that oxidative stress plays a role in the associations.